RECOGNIZING SILKWORM AS AN EXPERIMENTAL ANIMAL MODEL-A NON ETHICAL APPROACH - AMIT SRIVASTAVA; VENKATESH KUMAR R. (International Journal of Pharma and Bio Sciences, 2013)
Research and development over the years have flourished however of many constraints for the use of animals for testing and other purpose have put this very vibrating area to search for new alternatives. Mammals like mice and rats are chosen as model animals. But sacrificing large numbers of animal for experimental purpose has ethical constraints as well as technicalities in examining pharmacokinetics of drugs. To solve such problems, use of invertebrates models like Drosophila malanogaster and Caenorhabditis elegans has been reported. But due to their small body size they are found to be unsuitable for injection studies. The current article focuses on benefits of establishing silkworm as excellent model in present study systems when compared to other vertebrate and invertebrate models.